y = x^2 - 2x - 3
Factored Form: y = (x - 3)(x + 1)
X-Intercepts: (3, 0) and (-1, 0)
Axis of Symmetry: x = 1
Vertex: (1, -4)
Domain: All Real Numbers (or negative infinity to infinity)
Range: y > -4
Hope this helps!
Answer:
No
Step-by-step explanation:
12:15 can be simplified to 4:5
6:14 can be simplified to 3:7
These two are not equivalent to eachother
I think the answer is C.
First start by factoring, you should get (2n-3)(n-2)=0
Then start to solve for n.
2n-3=0
n-2=0
n=2, n= 3/2
I hope that helps.
Answer:
AC ≅ AE
Step-by-step explanation:
According to the SAS Congruence Theorem, for two triangles to be considered equal or congruent, they both must have 2 corresponding sides that are of equal length, and 1 included corresponding angle that is of the same measure in both triangles.
Given that in ∆ABC and ∆ADE, AB ≅ AD, and <BAC ≅ DAE, <em>the additional information we need to prove that ∆ABC ≅ ADE is AC ≅ AE. </em>This will satisfy the SAS Congruence Theorem. As there would be 2 corresponding sides that are congruent, and 1 corresponding angle in both triangles that are congruent to each other.
Answer:
2x + 1 = 15
Step-by-step explanation: